2020
DOI: 10.9734/jamb/2020/v20i230217
|View full text |Cite
|
Sign up to set email alerts
|

Overdose Administration of Thermostable Newcastle Disease Vaccines to Naïve Unvaccinated 6 Weeks Old Cockerels at NVRI, Vom Plateau state, Nigeria

Abstract: One hundred and fifty (150) unvaccinated 6 weeks old cockerel were divided into six groups of 25 birds each. Pre-vaccination haemagglutination inhibition (HI) mean titers values of 21.4, <21, 21 <21   21 and 21.6 were observed for groups A, B, C, D E and F respectively. Two batches of Newcastle Disease vaccine (NDVI-2) of 50 and 200 doses produced at National Veterinary Research Institute Vom, with EID50 value of 7.7 and 7.6 per dose were administered to groups B and D at 10x (10 times the normal dose) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Therefore, due to extra Log 10 EID50 values per dose in-cooperated in each of these vaccine batches originally by the producers, the vaccine dose value was still within acceptable dose per range for NDVI-2 despite the obvious titre loss or drop after certification. Field vaccination control strategy for Newcastle disease outbreak in susceptible poultry flock is only achievable by the use of field fit, safe, efficacious and wholesome Newcastle disease vaccines [15], especially in endemic region. The findings of our study demonstrated that prolonged extended transportation of a naturally thermostable vaccine with poor cold condition maintianance can result in loss of EID50 titre per dose value.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, due to extra Log 10 EID50 values per dose in-cooperated in each of these vaccine batches originally by the producers, the vaccine dose value was still within acceptable dose per range for NDVI-2 despite the obvious titre loss or drop after certification. Field vaccination control strategy for Newcastle disease outbreak in susceptible poultry flock is only achievable by the use of field fit, safe, efficacious and wholesome Newcastle disease vaccines [15], especially in endemic region. The findings of our study demonstrated that prolonged extended transportation of a naturally thermostable vaccine with poor cold condition maintianance can result in loss of EID50 titre per dose value.…”
Section: Resultsmentioning
confidence: 99%